Best available techniques in the fertilizer production industry: A Review - Gezerman, Ahmet Ozan; Çorbacıoğlu, Burcu Didem (European Journal of Chemistry, 2016)
Treatment and disposal of emission gases used for fertilizer production are among the most pressing issues in the modern fertilizer industries. Associations such as the European Manufacturer Association are developing new techniques, i.e., best available techniques, to resolve such problems. Best available techniques have been developed by the European Manufacturer Association to standardize the solutions to common problems encountered in the fertilizer industry, such as optimization of pH, pressure, temperature, nitrogen content, and fertilizer particle size. The best available techniques aim at minimizing greenhouse gas emissions in the fertilizer industry as well as wastewater treatment and waste management. The high operation and investment costs in the fertilizer industry have prompted manufacturers to consider the application of the best available techniques.